The Transmission of Arabic Knowledge Through Madrasa Systems: A Historical Study / نقل المعرفة العربية من خلال نظام المدارس: دراسة تاريخية - Yunus Al-Faruqi; Laila Hasanah (IJAS: International Journal of Arabic Studies, 2025)
This study explores the historical transmission of Arabic knowledge through the madrasa system, focusing on its role in shaping Islamic education and preserving intellectual traditions. The research investigates how madrasas emerged as centers of learning that integrated language, religion, and cultural values, thereby ensuring the continuity of Arabic as both a scholarly and religious language. Using historical analysis and a qualitative approach, the study traces the development of madrasas from their origins in the early Islamic period to their expansion across different regions of the Muslim world. It also examines the pedagogical strategies employed in teaching Arabic, the curriculum structure, and the scholarly networks that contributed to knowledge dissemination. The findings highlight that madrasas were not only educational institutions but also cultural hubs that promoted social cohesion, intellectual exchange, and the preservation of classical Arabic texts. Furthermore, the study reveals the continuing relevance of madrasa-based education in modern contexts, especially in balancing tradition with contemporary educational needs. Ultimately, this research contributes to a deeper understanding of the historical foundations of Arabic education and its enduring impact on Islamic civilization.